Reimagining the European Family - Simpson, P. author. aut Link
XI, 189 p.
Keywords: Re-imagining the Family explores contemporary films and literature about the effects of legal and illegal immigration on the structure and the stories of the contemporary 'European' family, with a focus on Germany.